Insights on the relaxation of liposomes encapsulating paramagnetic Ln‐based complexes. Issue 2 (3rd September 2014) - Mulas, Gilberto; Ferrauto, Giuseppe; Dastrù, Walter; Anedda, Roberto; Aime, Silvio; Terreno, Enzo
<x xml:space="preserve">Abstract</x> Purpose: To describe and quantify the different relaxation mechanisms operating in suspensions of liposomes that encapsulate paramagnetic lanthanide(III) complexes. Theory and Methods: The transverse relaxation rate of lanthanide‐loaded liposomes receives contribution from the exchange between intraliposomal and bulk water protons, and from magnetic susceptibility effects. Phospholipids vesicles encapsulating different Ln(III)‐HPDO3A complexes (Ln = Eu, Gd, or Dy) were prepared using the conventional thin film rehydration method. Relaxation times (T1, T2, and T2*) were measured at 14 Tesla (T) and 25°C. The effect of compartmentalization of the paramagnetic agent inside the liposomal cavity was evaluated by means of an IRON‐modified MRI sequence. Results: NMR measurements demonstrated that Curie spin relaxation is the dominant contribution (> 90%) to the observed transverse relaxation rate of paramagnetic liposomes. This was further confirmed by MRI that showed the ability of the liposome entrapped lanthanide complexes to generate IRON‐MRI positive contrast in a size dependent manner. Conclusion: The Curie spin relaxation mechanism is by far the principal mechanism involved in the T2 shortening of the water protons in suspension of paramagnetic liposomes at 14T. The access to IRON contrast extends the potential of such nanosystems as MRI contrast agents. Magn Reson Med 74:468–473, 2015. © 2014 Wiley Periodicals, Inc.